Descartes on the Intellectual Nature of Human Sense Perception: From the Innermost Self to the Material World - Gómez-Alonso, Modesto Manuel (Analysis. Journal of Philosophical Research, 2015)
In this essay, I argue that a proper understanding of the Cartesian proof of the external world sheds light on some vexatious questions concerning his theory of sense perception. Three main points emerge from the discussion: a picture of the mind, conceived as the power of understanding, as essentially related to the physical world; an extension of rationality such as it includes a set of necessities that neither can be deduced from the principles furnished by pure understanding alone nor are to be found among the particular items of sense experience; and a conception of human sense perception as a composite power that includes sensory awareness as well as understanding, and so that establishes a sharp distinction between human and animal sensory awareness. As far as agency is a constitutive ingredient of human sense perception, Descartes’ doctrine is in line with some current versions of a virtue epistemology.